1998
DOI: 10.1076/opge.19.2.69.2318
|View full text |Cite
|
Sign up to set email alerts
|

A syndrome of retinitis pigmentosa, congenital ichthyosis, hypergonadotropic hypogonadism, small stature, mental retardation, cranial dysmorphism, and abnormal electroencephalogram

Abstract: The association of retinitis pigmentosa, congenital ichthyosis, hypergonadotropic hypogonadism, small stature, mental retardation, cranial dysmorphism, and abnormal electroencephalogram may represent a distinct syndrome previously considered a subset of the now defunct Rud syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Extremely high concentrations (millimolar levels) of phytanic acid can be found in some disease states such as the Refsum's disease or Zellweger syndrome, where dysfunction of phytanic acid a-oxidation leads to an accumulation of phytanic acid in human blood and tissues (Steinberg 1995;Verhoeven et al 1998). Interestingly, patients with these disorders displayed similar symptoms to those described for vitamin A deficiency or hypervitaminosis A, such as retinitis pigmentosa and ichthyosis (Kaufman 1998;Stu¨ttgen 1982;Van Soest et al 1999). It was also demonstrated that the precursor phytol is bioactivated to phytanic acid in several species (Hansen et al 1966;Klenk and Kremer 1965;Mize et al 1966;Steinberg et al 1966;Stoffel and Kahlke 1965).…”
Section: Introductionmentioning
confidence: 79%
“…Extremely high concentrations (millimolar levels) of phytanic acid can be found in some disease states such as the Refsum's disease or Zellweger syndrome, where dysfunction of phytanic acid a-oxidation leads to an accumulation of phytanic acid in human blood and tissues (Steinberg 1995;Verhoeven et al 1998). Interestingly, patients with these disorders displayed similar symptoms to those described for vitamin A deficiency or hypervitaminosis A, such as retinitis pigmentosa and ichthyosis (Kaufman 1998;Stu¨ttgen 1982;Van Soest et al 1999). It was also demonstrated that the precursor phytol is bioactivated to phytanic acid in several species (Hansen et al 1966;Klenk and Kremer 1965;Mize et al 1966;Steinberg et al 1966;Stoffel and Kahlke 1965).…”
Section: Introductionmentioning
confidence: 79%
“…Anecdotal case reports include a 3-year-old boy with postnatal growth failure, microcephaly, developmental delay, minor facial anomalies, evolving pigmentary retinopathy, pituitary hypoplasia, micropenis, and growth GH deficiency diagnosed as microcephalic osteodysplastic slender-bone disorder by Maclean et al [2002]. Kaufman [1998] described two unrelated women with a disorder of RP, congenital ichthyosis, hypergonadotropic hypogonadism, small stature, mental retardation, cranial anomalies, and abnormal electroencephalograms. Additional syndromes involve renal abnormalities such as Senior-Loken syndrome complicated by nephrolithiasis and renal failure [Rivolta et al, 2002].…”
Section: Discussionmentioning
confidence: 98%
“…There were no neurological de®cits suggestive of either Refsum disease or Sjogren-Larsson syndrome in this family. Rud syndrome was formerly considered to be a genetically heterogeneous but distinct clinical entity with the manifestations of ichthyosis, hypogonadism, small stature, mental retardation, epilepsy and, infrequently, retinitis pigmentosa [Kaufman, 1998]. The existence of such a syndrome, however, has been recently disputed, based on a new understanding of the ichthyoses.…”
Section: Discussionmentioning
confidence: 98%
“…The existence of such a syndrome, however, has been recently disputed, based on a new understanding of the ichthyoses. Most cases previously reported as Rud syndrome can now be reassigned under a contemporary ichthyosis classi®cation that does not include Rud syndrome as a distinct entity [Kaufman, 1998]. Major diagnostic criteria for the Rud syndrome were ichthyosis, hypogonadism, mental retardation, and epilepsy [Munke et al, 1983].…”
Section: Discussionmentioning
confidence: 99%